2019
DOI: 10.1111/bjh.15903
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasma exchange in the management of autoimmune disorders

Abstract: Summary Therapeutic plasma exchange (TPE) has been mainly used in the treatment of autoimmune diseases. The main mechanisms of action of TPE include the removal of circulating autoantibodies, immune complexes, complement components, cytokines and adhesion molecules, along with sensitization of antibody‐producing cells to immunosuppressant agents. TPE is useful in autoimmune haematological, renal, rheumatic and neurological diseases, and is recommended for acute disorders, together with relapsed or worsened chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 87 publications
0
28
0
2
Order By: Relevance
“…Some published papers indicated that other mechanisms include the removal of circulating immune complexes, complement components, cytokines, and adhesion molecules; the replacement of missing plasma components; alteration of the numbers of immune cells and the function of regulatory T cells (Treg) and natural killer cells; and sensitization of antibody-producing cells to immunosuppressant agents. [16][17][18] Prior studies have evaluated the role of cytokines/chemokines in AE. Anti-NMDAR encephalitis patients showed distinct CSF interleukin-17 (IL-17)A/IL-6 axis activation, which might promote intrathecal antibody synthesis, resulting in delayed responses after immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some published papers indicated that other mechanisms include the removal of circulating immune complexes, complement components, cytokines, and adhesion molecules; the replacement of missing plasma components; alteration of the numbers of immune cells and the function of regulatory T cells (Treg) and natural killer cells; and sensitization of antibody-producing cells to immunosuppressant agents. [16][17][18] Prior studies have evaluated the role of cytokines/chemokines in AE. Anti-NMDAR encephalitis patients showed distinct CSF interleukin-17 (IL-17)A/IL-6 axis activation, which might promote intrathecal antibody synthesis, resulting in delayed responses after immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…TPE is used to remove antibodies and immune complexes from circulation [11]. It is the standard of care in thrombotic thrombocytopenic purpura, in which it removes ADAMTS13-blocking antibodies [12].…”
Section: Discussionmentioning
confidence: 99%
“…TPE can clear pro-and anti-inflammatory cytokines, growth factors, beneficial immunoglobulins, coagulation factors, antibiotics, and toxins. [93][94][95] Patients with liver failure are distinctly different as compared with other immune-mediated diseases. The liver has a unique potential to regenerate, and there is a lack of pathogenic autoantibodies compared with other immune-mediated conditions.…”
Section: Prescription For Therapeutic Plasma Exchange: Deciding the Exchange Volume And Intensitymentioning
confidence: 99%